Tratamento de derivativos de balcão em casos de insolvência bancária: balanceamento entre a liquidez das partes e a estabilidade sistêmica - Lima, Bernardo Kruel de Souza (2017)
This paper aims to analyse what should be the appropriate treatment to over-the-counter derivatives in case of bank insolvency. Whit that in mind, this dissertation aims to balance the liquidity to the counterparts of financial institutions in recovery procedures and seek for effective recovery of the banks. On one hand, the broad permission for early termination of over-the-counter derivatives allows liquidity to the insolvent institution's counterparties and restricts their credit risk. However, the early termination of large contract at the same time can destabilize the market, generate fire sales, and affect other institutions, increasing systemic risk. On the other hand, preventing the settlement of contracts between financial institutions (in case one is in the process of being recovered) can generate a liquidity crisis, and consequently a decrease in the number of operations, which also increases the systemic risk. In this sense, what is sought to analyse in this work is how to balance these two concerns and how the creation of a short stay period can help in the recovery of financial institutions without imposing losses to their counterparts.